Large-Scale Mechanochemical Synthesis of Cesium Lanthanide Chloride for Radioluminescence - Samanta, Tuhin; Han, Joo Hyeong; Lee, Han Uk; Cha, Bo Kyung; Park, Yong Min; Viswanath, Noolu Srinivasa Manikanta; Cho, Han Bin; Kim, Hyeon Woo; Cho, Sung Beom; Im, Won Bin (Inorganic Chemistry, 2024)
Cesium lanthanide chloride (Cs3LnCl6), a recently developed class of lanthanide-based zero-dimensional metal halides, has garnered a significant amount of interest because of its potential applications in scintillators, light-emitting diodes, and photodetectors. Although cesium lanthanide chloride demonstrates exceptional scintillator properties, conventional synthesis methods involving solid-state and solution-phase techniques are complex and limited on the reaction scale. This study presents a facile mechanochemical synthesis method for producing Cs3CeCl6, Cs3TbCl6, and Cs3EuCl6 metal halides on a 5 g scale. These materials exhibit intense blue-violet, green, and red emissions upon ultraviolet excitation, with high photoluminescence quantum yields ranging from 54% to 93%. Furthermore, Cs3CeCl6, Cs3TbCl6, and Cs3EuCl6 metal halides exhibit intense radioluminescence spanning from the ultraviolet to the visible region. This research shows the potential of the scalable mechanochemical synthesis of lanthanide-based metal halides for the advancement of luminescent materials for scintillators.
Keywords: Conventional synthesis; Large-scales; Lightemitting diode; Mechanochemical synthesis; Radio-luminescence; Scintillator properties; Solid-state phasis; Solution phase; Synthesis method; Zero-dimensional